Bringing the Ocean to the Stage: Performing Coastal Values and Marine Management - Emma McKinley; Erika Hughes; Stephenie Georgia; Cressida Bowyer; Kathryn Fradera; Alison Fairbrass; Jonathan Potts (Ocean and Society)
Recent years have witnessed a seemingly constant call for improved understanding of human–ocean relationships, resulting in a “boom” of marine social science research, sometimes framed through the lens of ocean literacy. Defined as having an understanding of your influence on the ocean, and its influence on you, ocean literacy has gained traction in recent years as a way of better understanding the complexities of human–ocean relationships. However, despite this interest in the human dimensions of the ocean, coasts and seas, and a corresponding increase in broader marine social sciences research, qualitative and arts‐based research approaches continue to remain on the periphery of ocean research. This article explores the role of two ocean research “outliers,” intersecting arts‐based practice and marine social sciences through the lens of interconnected performances designed to explore the diverse values held by communities about their marine and coastal environment. Undertaken as part of the Diverse Marine Values project, the performances brought together ocean scientists, coastal and marine managers, and community members to create original performance pieces in Lerwick, Shetland, Scotland, and Portsmouth, England. Drawing heavily on applied theatre practice and scholarship, these distinct but interrelated performances utilised elements of forum theatre, devised theatre, and storytelling to address marine issues important to each respective community, with a view to understanding and fostering ocean literacy. In each location, the performance work illustrated ways in which theatre can serve as not only a tool for science communication, but also a research method to explore a range of ocean literacy dimensions. The performances helped the research team, comprised jointly of specialist theatre practitioners and experts in ocean literacy, coastal management, and plastics pollution to reshape data collection and stakeholder engagement. This collaborative theatre‐making process led to deeper conversations and embedded engagement within each coastal community. It also led to a fundamental reshaping of the questions and approaches that the marine managers and scientists asked of the communities in question. The article presents a discussion of the challenges of bridging these related, but often distant, disciplines, and highlights the role of arts‐based research practice in broader ocean literacy research and discourse.